Evaluation of the advantages and progressions of water transport: a bibliometric review - Oliveira, Julya; Madeira, Carolina Lordes; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2024)
Due to its high transport capacity, low operating costs and lower environmental impact than other options, water transport in Brazil has become a viable and sustainable option for cargo transport. The ProKnow-C methodology was used in this study to examine the advancement of this modal, as well as its advantages and disadvantages. The results show that waterway transport reduces pollutant emissions, offers greater safety for cargo and facilitates integration with other types of transport. However, inadequate infrastructure, excessive bureaucracy and the need for greater multimodal integration are some of the problems the sector still faces. The full efficiency of the modal is limited by these factors, but the mitigation of these problems and the sustainable expansion of waterway transport in Brazil can be achieved through investments in infrastructure and appropriate public policies. The study concludes that water transport has immense potential to help the country's economic and environmental development, despite the challenges.
Keywords: Water transportation; Progress; Benefits; ProKnow-C